Cryotherapy reduces muscle hypertonia, but does not affect lower limb strength or gait kinematics post-stroke: a randomized controlled crossover study - Alcantara C.C. (2019)
© 2019, © 2019 Taylor & Francis Group, LLC.Background: Based on the premise that spasticity might affect gait post-stroke, cryotherapy is among the techniques used to temporarily reduce spasticity in neurological patients. This effective technique would enhance muscle performance, and ultimately, functional training, such as walking. However, understanding whether a decrease in spasticity level, if any, would lead to improving muscle performance and gait parameters is not based on evidence and needs to be clarified. Objectives: to investigate the immediate effects of cryotherapy, applied to spastic plantarflexor muscles of subjects post-stroke, on tonus level, torque generation capacity of plantarflexors and dorsiflexors, and angular/spatiotemporal gait parameters. Methods: Sixteen chronic hemiparetic subjects participated in this randomized controlled crossover study. Cryotherapy (ice pack) or Control (room temperature sand pack) were applied to the calf muscles of the paretic limb. The measurements taken (before and immediately after intervention) were: 1) Tonus according to the Modified Ashworth Scale; 2) Torque assessments were performed using an isokinetic dynamometer; and 3) Spatiotemporal and angular kinematics of the hip, knee, and ankle (flexion/extension), obtained using a tridimensional movement analysis system (Qualisys). Results: Cryotherapy decreased plantarflexor tonus but did not change muscle torque generation capacity and did not affect spatiotemporal or angular parameters during gait compared to control application. These findings contribute to the evidence-based approach to clinical rehabilitation post-stroke. Conclusions: The findings of this study suggest that cryotherapy applied to the calf muscles of subjects with chronic hemiparesis reduces muscle hypertonia but does not improve dorsiflexors and plantarflexors performance and gait parameters.